2005
DOI: 10.1007/s00467-005-1998-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective cyclo-oxygenase inhibitors and glomerular filtration rate in preterm neonates

Abstract: The adverse effects of nonselective cyclo-oxygenase (COX) inhibitors on the immature kidney have been described in newborn rabbits, but it is much more laborious and difficult to study its relative impact on renal function in human neonates. Amikacin clearance was therefore used as surrogate marker to study the impact of nonselective COX-inhibitors on glomerular filtration rate. Clinical characteristics and amikacin clearance of infants on respiratory support were retrospectively collected. Results in neonates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…We found a positive correlation between amikacin clearance and GA, as has been described for aminoglycosides (18,20,(35)(36)(37)(38)(39). The absolute value of amikacin clearance (0.61 ml/kg per min) is comparable to previously reported values (0.52 to 0.6 ml/kg per min (17)(18)(19)40). Also, the distribution volume of amikacin was similar to previously reported values of 0.58 L/kg (18) and 0.59 L/kg (17).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found a positive correlation between amikacin clearance and GA, as has been described for aminoglycosides (18,20,(35)(36)(37)(38)(39). The absolute value of amikacin clearance (0.61 ml/kg per min) is comparable to previously reported values (0.52 to 0.6 ml/kg per min (17)(18)(19)40). Also, the distribution volume of amikacin was similar to previously reported values of 0.58 L/kg (18) and 0.59 L/kg (17).…”
Section: Discussionsupporting
confidence: 90%
“…Previously, the clearance of amikacin was used as a marker of GFR in neonates (17)(18)(19)(20) because aminoglycoside clearance correlates well with GFR (21). Amikacin is often used in neonates in whom perinatal infection is suspected, and amikacin levels are routinely monitored.…”
mentioning
confidence: 99%
“…22 We have also found that in infants with hsPDA, SeCr increase preceded ibuprofen administration, this suggesting that a renal impairment because of PDA and/or associated conditions exists before starting NSAID therapy. Concerning this point, many studies demonstrated that prophylactic or therapeutic ibuprofen, as with other cyclooxygenase inhibitors, may not be exempt from causing renal adverse effects, [23][24][25] but few investigations have explored the effect on renal function of PDA before and independently from ibuprofen treatment. Vanpée et al 26 showed that sick VLBW infants having a PDA and requiring mechanical ventilation had lower creatinine clearances and significantly higher fractional sodium excretion than controls; however, their study also included few infants who had received NSAID for ductus closure before evaluating renal function.…”
Section: Discussionmentioning
confidence: 99%
“…NsNSAIDs affect renal blood flow, glomerular filtration and renal drug clearance (Allegaert, Vanhole et al, 2005). Renal failure in association with nsNSAID use has occurred in neonates (Andreoli, 2004) and older children (Taber & Mueller, 2006), usually in the setting of other haemodynamic compromise.…”
Section: Note: Reversal Of Conclusionmentioning
confidence: 99%
“…Neonatal bolus and short-term use for patent ductus arteriosus closure can produce pulmonary hypertension and alterations in cerebral (Naulaers et al, 2005), gastrointestinal and renal blood flow (Allegaert, Vanhole et al, 2005;Aranda & Thomas, 2006). Relative effects of indomethacin (indometacin) and ibuprofen on the risk of intraventricular haemorrhage continue to be debated (Aranda et al, 1997;Ment et al, 2004).…”
Section: Note: Reversal Of Conclusionmentioning
confidence: 99%